RASIO PAJAK OPTIMAL DAN TINGKAT PERTUMBUHAN EKONOMI DI INDONESIATAHUN 1970-2008 - Setiabudi, Andang Wirawan (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
Many economists have stated that the government through its either fiscal policies or monetary policies has an important role in supporting economic growth of a country. As the consequence of government’s role in the development process, the size of the government – measured as the ratio of total spending to GDP also expanded along with the economic development. This is the fact faced by any country in the world. However, the growth of government’s size implies higher taxation, and thus, it sometimes become a bad sign for the whole economy. The higher tax collected by the government the more productive source taken by the government from the private sector. If positive impacts of government spending cannot exceed negative impact caused by the lost of productive source of private sectors deadweight loss of economy will appear. By assuming that government runs balanced budget in which all of the government expenditure is financed by tax revenue, so the growth maximizing tax ratio can be estimated. This rate measures the ratio of tax revenue to GDP that is needed to achieve the high and stable growth rate.        The main objective of this study are to find the growth maximizing tax ratio for Indonesia and to analyze whether Indonesia has achieved this optimum point, or has been operating below it or contrary above it. The regression result show that the growth maximizing tax ratio for Indonesia is 14,64%.